2020
DOI: 10.1080/02602938.2020.1765228
|View full text |Cite
|
Sign up to set email alerts
|

Formative assessment as practice: the role of students’ motivation

Abstract: Formative assessment can be seen as an integral part of teaching and learning, as formative assessment affects students' learning and vice versa. Students' motivation can theoretically be placed at the centre of this reciprocal relationship, as formative assessment is assumed to affect students' need satisfaction of autonomy, competence and relatedness, and consequently their autonomous motivation. In the current study, two assumptions were tested empirically: formative assessment contributes to students' auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 49 publications
3
52
0
9
Order By: Relevance
“…In the measurement tradition, formative assessment is often explained as a contrast to summative assessment. Formative assessment is about low-stakes testing, whereas summative assessment concerns highstakes testing [2]. However, assessments with a summative or a formative purpose are both used to produce inferences about students' learning.…”
Section: Formative E-assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the measurement tradition, formative assessment is often explained as a contrast to summative assessment. Formative assessment is about low-stakes testing, whereas summative assessment concerns highstakes testing [2]. However, assessments with a summative or a formative purpose are both used to produce inferences about students' learning.…”
Section: Formative E-assessmentmentioning
confidence: 99%
“…In other words, when assessment is looked as a formative practice, teachers and the students have their roles realized in the process of learning. In practice, formative assessment is seen as a cyclical program of high and low-stake tasks in which students are actively involved both as assessee and/or assessor [2].…”
Section: Formative E-assessmentmentioning
confidence: 99%
“…The formative and shared assessment processes seek to make the students aware and responsible for their achievements, relate them to the competences to be developed and enable them to make autonomous and contextualized progress in their learning [65,[69][70][71][72][73][74]. This leads us to obtain results as positive as those indicated by Leenknecht, Wijnia, Köhlen, Fryer, Rikers and Loyens [75], who have demonstrated that the practice of a formative assessment with students generates in them a feeling of competence and autonomous motivation, or other studies [76][77][78], which corroborated the importance of formative assessment for increasing student involvement and responsibility. In this sense, we can find transferable practical experiences of formative and shared assessment, capable of generating motivation and responsibility in students through the development of their autonomy, such as the one presented by Pérez-Pueyo, Hortigüela-Alcalá and Hernando-Garijo [79].…”
Section: The Role Of Assessment In Promoting the Motivation And Involmentioning
confidence: 99%
“…Formative assessment has become a well-known and important concept in education and research (Black and Wiliam 2018;Schildkamp et al 2020). Formative assessment is defined as a process of constant interaction between students and teacher (Black and Wiliam 2012), and should be viewed as an integral part of teaching and learning (Leenknecht et al 2021). However, formative assessment approaches are not regularly adopted in classroom practice (Robinson et al 2014;Boud et al 2018).…”
Section: Introductionmentioning
confidence: 99%